Microstructure and Properties of Super-Ferritic Stainless Steels Used for Marine Construction after Fire Exposure - Ke-Yu Shen (Advances in Materials Science and Engineering, 2022)
In this paper, the super-ferritic stainless steels (SFSSs) were simulating treated in a fire accident, and their mechanical properties and corrosion performance before/after fire exposure were studied. The experimental results demonstrated that SFSSs have a good combination property with the tensile strength, total elongation, and corrosion rate in FeCl3 solution of ∼600 MPa, ∼22.5%, and 0.03 mm/a. After fire exposure, the mechanical properties and corrosion performance were affected based on the exposure temperature due to the precipitation of intermetallic compounds. When the fire exposure temperature was 700–800°C, the plasticity was exasperated and the value decreased to only 1.5% at the condition of 800°C × 4 h due to the bulk σ-phase precipitation at grain boundaries. Meanwhile, the brittle fracture patterns emerged, and the corrosion rate in FeCl3 solution increased to 0.4 mm/a. When fire exposure takes place at 600°C for less than 4 h, the mechanical properties and the corrosion performance were little affected. Thus, it was possible to use SFSSs in marine environments.